2018
DOI: 10.22410/issn.1983-0378.v39i1a2018.1837
|View full text |Cite
|
Sign up to set email alerts
|

A Era Dos Avós Contemporâneos Na Educação Dos Netos E Relações Familiares: Um Estudo De Caso Na Universidade Da Maturidade Da Universidade Federal Do Tocantins

Abstract: Neste artigo, narramos as práticas educativas realizadas entre os avós do projeto UMA e seus netos. Será exposto como os avós acadêmicos compreendem essa nova realidade social que modifica o quadro familiar do século XXI. É uma pesquisa descritiva com abordagem qualitativa com a forma de Estudo de Caso e uma análise de conteúdo. Concluiu-se que é contemporâneo ser avô ativo, por isso, essa inovada função social deve ser estudada e refletida nas famílias entre todas as gerações para se evitarem conflitos interg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 1 publication
1
3
0
19
Order By: Relevance
“…The transformations that have been taking place in contemporary times, such as the departure of women into the labor market, changes in gender and parental roles, have shown that the roles of mediators have been transformed, since fathers and mothers are forced to share their time between work and taking care of the home and children.31 Grandparents are often called upon to exercise this function, either partially or in full. 32 The family environment is considered privileged for the constitution of psychic life, complete and cultural development, and intergenerational transmission, which provides support for the individual and social formation of human beings. Grandparents tend to be the main responsible for the transmission of these values in the relationship with their grandchildren, and the maternal or paternal functions previously exercised by them can influence the role of grandfather to be conflicting or satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…The transformations that have been taking place in contemporary times, such as the departure of women into the labor market, changes in gender and parental roles, have shown that the roles of mediators have been transformed, since fathers and mothers are forced to share their time between work and taking care of the home and children.31 Grandparents are often called upon to exercise this function, either partially or in full. 32 The family environment is considered privileged for the constitution of psychic life, complete and cultural development, and intergenerational transmission, which provides support for the individual and social formation of human beings. Grandparents tend to be the main responsible for the transmission of these values in the relationship with their grandchildren, and the maternal or paternal functions previously exercised by them can influence the role of grandfather to be conflicting or satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, a study carried out with 30 elderly people who took part in a further study product at the University of Maturity at the Universidade Federal do Tocantins, 70% of whom have legal and financial custody of their grandchildren, showed, in declarations made by the participants, that having an extended role has a positive effect, through a feeling of personal renewal and that one has done one's duty, but may also have a negative effect, through possible conflicts and financial burden 29 .…”
Section: Relations Of Reciprocity and Healthy Coexistence Between Adomentioning
confidence: 99%
“…Findler (2000) destaca que a rede de profissionais poderia se beneficiar mais dos avós, os quais representam um recurso importante de apoio e que, muitas vezes, não são solicitados mesmo estando disponíveis. Entretanto, estudos indicam que, em grande parte, os avós desempenham um papel secundário na escolaridade dos netos, indicando que a monitoria e supervisão no que se refere a acompanhamento escolar fica a cargo dos pais (Silva, 2010;Mitchell, 2008) A literatura tem mostrado a presença dos avós guardiões, principalmente, em famílias compostas por, pelo menos, um dos pais, os avós e as crianças (Dias et al, 2010;Osório, et al 2018), bem como naquelas com pais ausentes, nas quais cabe aos avós o cuidado completo dos netos (Dias et al, 2010;Mainette & Wanderbroocke, 2013;Souza, Castro, Araújo & Santos, 2018). Osório et al (2018), em uma pesquisa com avós participantes de um projeto de extensão da Universidade da Maturidade vinculado à Universidade Federal do Tocantins, identificaram que, de um total de 30 participantes, 70% eram totalmente responsáveis pelos cuidados dos netos, inclusive financeiramente.…”
Section: Os Estudos Sobre Avós 1 : Um Panorama Geralunclassified
“…Entretanto, estudos indicam que, em grande parte, os avós desempenham um papel secundário na escolaridade dos netos, indicando que a monitoria e supervisão no que se refere a acompanhamento escolar fica a cargo dos pais (Silva, 2010;Mitchell, 2008) A literatura tem mostrado a presença dos avós guardiões, principalmente, em famílias compostas por, pelo menos, um dos pais, os avós e as crianças (Dias et al, 2010;Osório, et al 2018), bem como naquelas com pais ausentes, nas quais cabe aos avós o cuidado completo dos netos (Dias et al, 2010;Mainette & Wanderbroocke, 2013;Souza, Castro, Araújo & Santos, 2018). Osório et al (2018), em uma pesquisa com avós participantes de um projeto de extensão da Universidade da Maturidade vinculado à Universidade Federal do Tocantins, identificaram que, de um total de 30 participantes, 70% eram totalmente responsáveis pelos cuidados dos netos, inclusive financeiramente. Coelho e Dias (2015) realizaram uma revisão sistemática de literatura sobre avós guardiões, no período de 2004 a 2014, e os resultados mostram que o relacionamento destes com seus netos é uma temática frequente nos estudos e sugerem forte vínculo afetivo entre eles.…”
Section: Os Estudos Sobre Avós 1 : Um Panorama Geralunclassified
See 1 more Smart Citation